Automatic waste classification using deep learning and computer vision techniques - Akash, MD.; Shama, Umme Sabiha; Dibash, Dey; Ghosh, Ria (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.